Kelayakan Biology Magazine Jamur Lokal Kalimantan Barat Sebagai Media Pembelajaran - Chintia Vani; Laili Fitri Yeni; Anisyah Yuniarti; Hayatul Fajri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
This study aimed to develop a printed magazine as a learning medium based on local potential that integrates morphological and phylogenetic characterization of fungi as a contextual learning resource. The research employed a Research and Development (R&D) approach following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), with the scope limited to the needs analysis, design, and development stages. The primary focus of the study was to produce a theoretically valid and feasible instructional product. Media feasibility was evaluated through expert validation involving five specialists using an assessment instrument covering language, content, and graphical aspects. Content validity was analyzed using the Content Validity Ratio (CVR). The results demonstrated a mean CVR value of 0.99, indicating a very high level of validity across all assessed aspects. The developed magazine was found to present scientific information systematically, align with the Biology curriculum, and effectively represent local potential as a contextual learning resource. These findings suggest that locally based magazines constitute a feasible instructional innovation for enriching biodiversity education.